1998
DOI: 10.1002/(sici)1097-0096(199806)26:5<231::aid-jcu1>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Breast masses: Color Doppler, power Doppler, and spectral analysis findings

Abstract: Purpose To determine the diagnostic efficacy of power Doppler sonography (PDS) with spectral analysis for breast diseases, we retrospectively compared PDS and color Doppler sonography (CDS) in patients with breast lesions. Methods One hundred thirty‐eight women with palpable breast lesions were examined with PDS (65 women) and/or CDS (73 women). We calculated peak velocity, end‐diastolic velocity, pulsatility index (PI), and resistance index (RI). Results On a 4‐point subjective visual vascularity scale, PDS d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…We previously reported that invasive carcinoma with marked fibrous stroma showed markedly increased PI. 7,30 We also found that PI, RI, and Vmin were well correlated with the degree of intratumor fibrous stroma in 54 invasive carcinomas. 30 The resistance of the intratumor blood flow is probably increased owing to significantly increased fibrous stroma in invasive breast carcinomas, such as scirrhous tumors.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…We previously reported that invasive carcinoma with marked fibrous stroma showed markedly increased PI. 7,30 We also found that PI, RI, and Vmin were well correlated with the degree of intratumor fibrous stroma in 54 invasive carcinomas. 30 The resistance of the intratumor blood flow is probably increased owing to significantly increased fibrous stroma in invasive breast carcinomas, such as scirrhous tumors.…”
mentioning
confidence: 71%
“…Owing to the lower angle dependence of PDS than CDS, PDS is more sensitive in the detection of vascular flow. [5][6][7] Tumor angiogenesis has been reported to play an important role in tumor growth and metastasis. 8,9 Recent studies have indicated that the MVD, as an overall marker of angiogenesis, is of prognostic value in many solid tumors.…”
mentioning
confidence: 99%
“…Doppler study was initially considered very promising in the differential diagnosis between benign and malignant masses on the basis of morphological criteria (number of penetrating vessels as well as central or peripheral distribution) and semiquantitative criteria (resistance and pulsatility indices, peak systolic velocity) which may identify the characteristic neoangiogenesis of malignant lesions [14e16]. Power Doppler is better than color Doppler for detecting small vessels with slow blood flow and is therefore able to distinguish between solid and complicated cystic lesions, but it is more sensitive to artifacts [17]. However, the literature has revealed a substantial overlap of aspects in the vascularity of benign and malignant lesions.…”
Section: Us Parameters In the Diagnosis Of A Probably Benign Lesionmentioning
confidence: 99%
“…In clinical breast sonography, much attention is focused on using vascularity as a diagnostic tool to differentiate between malignant and benign breast lesions. [15][16][17][18][19][20][21][22] This includes using both contrastenhanced ultrasound and using Doppler imaging alone. Gray scale boundary and echogenicity are still the main criteria used for assessing breast masses by ultrasonography.…”
Section: Figurementioning
confidence: 99%